Out‐of‐home care in childhood and biomedical risk factors in middle‐age: National birth cohort study. Issue 3 (5th November 2019) - de Mestral, Carlos; Bell, Steven; Hamer, Mark; Batty, George David
Abstract: Objective: With there being an apparent impact of experience of out‐of‐home care in childhood on chronic disease and mortality, we examined how such adversity might be embodied such that it has a measurable impact on human biology, so mediating this relationship. Methods: We used data from the UK National Child Development Study in which exposure to public care was prospectively gathered on three occasions up to age 16. Study members also participated in a social survey at age 42 and a clinical examination at age 44/45 when cardiovascular, inflammatory, neuroendocrine, and respiratory risk markers for mortality were collected, 19 of which were included as endpoints in the present analyses. Results: Of the 8012 participants in the biomedical survey, 4% ( n = 322) had been in care at some point in childhood and/or adolescence. We found the expected marked differences in the early life characteristics of poverty, health, and disability in children with experience of public care relative to their unexposed counterparts. After controlling for these confounding factors, however, care in childhood was essentially unrelated to biomarkers in middle‐age. We also found no consistent links between these biomarkers and the duration, timing, or type of care. Conclusions: Our results suggest that the biomarkers captured in the present study are unlikely to mediate the link between public care in childhood and later chronic disease or mortality. Processes involving mental health, socioeconomic position, and health behaviors would seem to be a potential alternative pathway warranting investigation.